2020
DOI: 10.3389/fneur.2020.00069
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Recovery From Cortical Blindness Caused by an Old Cerebral Infarction

Abstract: When the primary visual cortex (V1) is damaged, cortical blindness results. However, visual information obtained from the superior colliculus (SC) or direct thalamic afferents to higher visual cortices produces unconscious visual functions called blindsight. Alarming visual stimuli suggesting the approach of a predator are known to trigger escape behaviors via visual information mediated by the SC and amygdala in small animals, and salient and dynamic visual stimuli also produce some conscious visual experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…We planned self-training using the visual field test to improve the visual defects, since repeated presentation of appropriate visual stimuli may ameliorate visual defects in hemianopic patients ( 12 ). However, if an extra examiner is required to operate the visual field test, self-training is not possible.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We planned self-training using the visual field test to improve the visual defects, since repeated presentation of appropriate visual stimuli may ameliorate visual defects in hemianopic patients ( 12 ). However, if an extra examiner is required to operate the visual field test, self-training is not possible.…”
Section: Resultsmentioning
confidence: 99%
“…The increased stimulus detection after repeated presentation of visual stimuli ( Figure 4 ) suggested that some form of neural plasticity might be induced in the visual system ( 12 ). We further investigated the patient's visual functions in detail.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations